Strategic Investment Funds : Establishment and Operations - Divakaran, Shanthi; Halland, Håvard; Lorenzato, Gianni; Rose, Paul; Sarmiento-Saher, Sebastian (Washington, DC: World Bank, 2022)
Strategic investment funds (SIFs) have gained prominence over the past two decades as governments and other public sponsors globally have increasingly co-opted the investment fund model to further policy objectives. Since 2000, more than 30 SIFs have been formed at the national level, typically to boost economic growth through infrastructure or small and medium enterprise investment. In the current COVID-19 pandemic environment, governments have frequently turned to sovereign investment vehicles to address the economic effects of the pandemic, echoing the emergence of new SIFs in the aftermath of the global financial crisis. However, SIFs are not devoid of challenges, and the setup and operation of such funds can be fraught with risks, particularly in contexts of weaker governance, inadequate rule of law, and limited financial market regulation. The intent of Strategic Investment Funds: Establishment and Operations is to provide guidance to practitioners and policy makers considering a SIF model where little widely available, practice-based experience has been documented and disseminated. The book provides a reference for policy makers who are creating or strengthening the operations of SIFs, particularly as governments examine the value of such funds as a policy instrument in the aftermath of the COVID-19 pandemic.